2005
DOI: 10.1039/b500667h
|View full text |Cite
|
Sign up to set email alerts
|

Novel supramolecular charge-transfer systems based on bis(18-crown-6)stilbene and viologen analogues bearing two ammonioalkyl groups

Abstract: A series of new viologen analogues bearing two ammonioalkyl groups (2-4) were synthesized in order to study their complexation with bis(18-crown-6)stilbene (1b). Electronic spectroscopy and 1 H NMR measurements show that in acetonitrile, bis(crown) stilbene 1b forms highly stable 1 : 1 and 2 : 1 chargetransfer (CT) complexes with p-acceptors 2-4 owing to host-guest bonding. The influence of geometric and electronic factors on the complex formation constants are discussed. The structures of the supramolecular C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 25 publications
0
46
0
1
Order By: Relevance
“…1, curves 1 and 2). The hypsochromic shift of the LA band maximum is characteristic of the formation of host-guest complexes by the chromogenous crown compounds 19, 20 and, undoubtedly, is due to the electron acceptor influ ence of ammonium groups of C4 linked with the crown ether fragments of (E) 1 through the N + -H...O hydrogen bonds. No considerable changes in the intensity and shape of the LA band in the presence of C4 indicates a weak intermolecular interaction through the space of chro mophoric fragments of (E) 1 in the complexes with the butanediammonium ion.…”
mentioning
confidence: 99%
“…1, curves 1 and 2). The hypsochromic shift of the LA band maximum is characteristic of the formation of host-guest complexes by the chromogenous crown compounds 19, 20 and, undoubtedly, is due to the electron acceptor influ ence of ammonium groups of C4 linked with the crown ether fragments of (E) 1 through the N + -H...O hydrogen bonds. No considerable changes in the intensity and shape of the LA band in the presence of C4 indicates a weak intermolecular interaction through the space of chro mophoric fragments of (E) 1 in the complexes with the butanediammonium ion.…”
mentioning
confidence: 99%
“…Такое явление может объясняться анизотропным эффектом, возникающим при расположении метиле-новой цепочки диаммония вдоль хромофорной протя-женной молекулы лиганда. Подобный эффект для комплекса бис-18-краун-6-стильбенов с солями алканди-аммония описан в работе [15] . Для подтверждения данного предположения в ходе исследований были получены двумерные спектры ЯМР Рисунок 1.…”
Section: Complexation Of сRown Containing Bithiophene and Alkanediammunclassified
“…[25][26][27][28] In solution, these compounds are capable of self-assembling into supramolecular ground-state charge-transfer complexes that shows very high thermodynamic stability. For example, the lgK value for complex 20 in MeCN was estimated to be 9.08.…”
Section: Pet Luminosensorsmentioning
confidence: 99%
“…[27] It was found that Ca 2+ or Ba 2+ ions are able to displace the acceptor component in complex 20, which leads to the appearance of the intense luminescence from the metal complexed biscrown stilbene. [28] PET luminosensors with cation-triggered long-lived emission can be constructed on the basis of metalorganic luminophores. The Eu III complex 21 [29] in methanol is characterized by weak delayed metal-centred emission.…”
Section: Pet Luminosensorsmentioning
confidence: 99%